Al-Qur’an dan Misteri Singularitas Awal: Telaah Tafsir Tematik Ayat-Ayat Kosmologis - Lulu Qutratu’aina (At-Ta'wil: Jurnal Pengkajian al-Qur'an dan at-Turats, 2025)
This research examines the mystery of the initial singularity of the universe—a central concept in the Big Bang theory—through a thematic analysis of cosmological verses in the Qur’an. The Big Bang theory states that the universe originated from an infinitely dense singularity but does not explain the conditions "before" it or its cause. Meanwhile, the Qur’an (e.g., QS. Al-Anbiya:30 and QS. Fussilat:11) describes the creation of the heavens and the earth in narratives rich with theological meaning. This study aims to: (1) Analyze how classical and contemporary exegeses interpret cosmological verses related to the beginning of creation, (2) Examine possible convergences or divergences between the concept of singularity and the Qur’anic descriptions, and (3) Assess the hermeneutical implications of this science-theology integration. The method used is thematic exegesis (tafsir maudhu’i) with an interdisciplinary approach (cosmology, philosophy of science, and Qur’anic studies). The findings indicate that some modern exegeses (such as those by Tantawi Jawhari or Maurice Bucaille) attempt to harmonize the singularity with Qur’anic verses, while classical exegeses emphasize symbolic aspects. These findings enrich the discourse on Islamic science while also critiquing both literalist and reductive scientific readings.